PEMASARAN DIGITAL MARKETING DALAM UPAYA MENINGKATKAN PENJUALAN HASIL PRODUK PERTANIAN - Ni Putu Ayu Kusumawati; Putu Cita Ayu; I Gede Aryana Mahayasa; Ni Putu Yeni Yuliantari; Gusti Alit Suputra (UNHI Press, 2026)
In the current digital era, the development of information technology is marked by the rise of smartphones as a digital communication media tool that can be used and its rapid development has an impact on society in supporting business activities, both small and large, in all sectors, especially the agricultural sector. Indonesia is an agricultural country with various agricultural products that are not commensurate with basic needs. Abundant agricultural products are accompanied by low selling prices at the farmer level due to the long distribution chain and farmers' dependence on middlemen. By introducing digital marketing to farmers which can connect farmers directly with consumers, with higher prices of course. The results achieved in the socialization activities regarding digital marketing in an effort to improve the marketing of Subak agricultural products are that Subak blahkiuh farmers understand how to use social media to market their products where after this socialization is carried out the farmers not only sell their products to collectors but can utilize social media. for maximum profit. The aim of socializing digital marketing for farmers is to increase farmers' knowledge about online marketing techniques. So that farmers are not technologically illiterate due to the increasingly advanced development of information technology, apart from that it can also increase the selling value of agricultural products so that it can increase the income of Subak farmers.